Allogeneic stem cell transplantation for blast crisis chronic myeloid leukemia in the era of tyrosine kinase inhibitors: a retrospective study by the EBMT Chronic Malignancies Working Party - Radujković, Aleksandar; Dietrich, Sascha; Blok, Henric-Jan (Biology of blood and marrow transplantation, 2019)
The prognosis of patients with blast crisis (BC) chronic myeloid leukemia (CML) is still dismal. Allogeneic stem cell transplantation represents the only curative treatment option, but data on transplant outcomes are scarce. We therefore conducted a retrospective, registry-based study of adult patients allografted for BC CML, focusing on patients with active disease at transplant and pretransplant prognostic factors. One hundred seventy patients allografted for BC CML after tyrosine kinase inhibitor pretreatment between 2004 and 2016 were analyzed. Before transplant, 95 patients were in remission, whereas 75 patients had active BC. In multivariable analysis of the entire cohort, active BC at transplant was the strongest factor associated with decreased overall survival (hazrd ratio, 1.87; P=.010) and shorter leukemia-free survival (LFS; hazard ratio, 1.69; P=.017). For patients with BC in remission at transplant, advanced age (≥45 years), lower performance status (≤80%), longer interval from diagnosis BC to transplant (>12 months), myeloablative conditioning, and unrelated donor (UD) transplant were risk factors for inferior survival. In patients with active BC, only UD transplant was significantly associated with prolonged LFS and trended toward improved overall survival. In summary, survival of patients allografted for BC CML was strongly dependent on pretransplant remission status. In patients with remission of BC, conventional prognostic factors remained the major determinants of outcome, whereas in those with active BC at transplant, UD transplant was associated with prolonged LFS in our study.